Hermit crabs as bioindicators of recent tributyltin (TBT) contamination - Sant'Anna, Bruno Sampaio [UNESP]; dos Santos, Dayana Moscardi; Sandron, Daniela Corsino [UNESP]; de Souza, Sara Cardoso [UNESP]; Rodrigues de Marchi, Mary Rosa [UNESP]; Zara, Fernando Jose [UNESP]; Turra, Alexander (Elsevier B.V., 2012)
Evaluation of the assimilation pathway and depuration time of a given pollutant by aquatic species is important to understand the dynamics of this substance in the biota, and to search for potential ecological indicators. In the present study, the uptake pathway and depuration time and rate of the pollutant tributyltin (TBT) were investigated in the omnivorous hermit crab (Clibanarius vittatus). The assimilation and uptake pathway were investigated using hermit crabs collected in an area free of TBT. The crabs were held in the laboratory for 45 days, under one of four treatments: procedural control (PC) - water and food without TBT; T1 - water with and food without TBT; 12 - water without and food with Tiff; and 13 water and food with TBT. To determine the depuration time, the crabs were collected in a contaminated area, maintained in the laboratory with clean water, and removed every 15 days for 120 days. The concentrations of TBT and DBT (dibutyltin) were determined by chromatographic analysis. The TBT was taken up by the crabs mainly via food, and the presence of DBT in crab tissues was hypothesized to result from internal TBT degradation. TBT (as well as DBT) was depurated rapidly by C. vittatus. After approximately 30 days, the initial concentration of 111 +/- 36 ng Sn g(-1) w. w. decreased to 3 +/- 3 ng Sn g(-1) w. w., and after 75 days the TBT concentration was below the detection limit. The same pattern was recorded for DBT, which showed a higher deputation rate than TBT. The rapid TBT and DBT deputation is useful information, since C. vittatus and possibly other hermit crabs may be used as indicators of recent or recycled environmental contamination. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Tributyltin (TBT); Hermit crab; Assimilation; Depuration; Ecological indicator